ChemInform Abstract: An Air‐ and Water‐Stable Iodonium Salt Promoter for Facile Thioglycoside Activation. Issue 36 (9th September 2014) - Chu, An‐Hsiang Adam; Minciunescu, Andrei; Montanari, Vittorio; Kumar, Krishna; Bennett, Clay S.
Abstract It is demonstrated that 2, 2, 2‐trifluoroethyl substituted iodonium salt promotes glycosylations at room temperature with both armed and disarmed thioglycosides as well as sensitive deoxy‐sugar donors.